Accurate and real-time network calculation for mine ventilation without wind resistance measurement. Issue 230 (November 2022) - Li, Junqiao; Li, Yucheng; Zhang, Jing; Li, Bolun; Zhang, Zhitao; Dong, Jinyang; Cui, Yunan
Abstract: A real-time correction method is proposed to accurately and comprehensively collect mine air volume data using wind velocity sensors; ventilation network calculation is realized without relying upon wind resistance measurements. For single-roadway wind velocity correction, an improved Kalman filter is employed to identify the error and adapt to dynamic changes in the ventilation system, improving the error updating process and thus the convergence rate. For node air mass flow balance correction, three types of sensor redundancy layouts are summarized with corresponding correction methods. The principle of the proposed real-time network calculation algorithm is discussed, the calculation method for each sensor layout is provided, and the robustness is analyzed accordingly. Simulation experiment results demonstrate significant improvements in the accuracy of the data obtained using the proposed data correction and network calculation algorithm. Thus, the designed real-time calculation algorithm can be practically applied to realize the accurate collection of ventilation data. Highlights: Single roadway and node air mass flow balance corrections are proposed for sensor data. A real-time network calculation method without wind resistance measurement is proposed. The robustness and checking method of the algorithm under different redundancy conditions are analyzed. Avoiding sensor blindness zone and breeze roadways allows high algorithm accuracy.